213 Credit scores as a novel measurement tool to examine violence inequities in Philadelphia, PA. (5th May 2020) - Uzzi, Mudia; Dean, Lorraine
Abstract : Statement of Purpose: Neighborhood Violence is a major social and public health issue throughout the United States and specifically in urban areas. Credit scores are an emerging novel measurement tool to examine violence across communities. Area-level credit scores reflect elements of neighborhoods' economic structure that is not captured by traditional socioeconomic position measures. Methods/Approach: Our ecological cross-sectional study obtained Census Block Group (CBG) Equifax Vantage 3.0 credit score averages for all CBGs (n=1, 325) in Philadelphia, PA from 2013–2017. We joined credit score data with geocoded data from 78, 184 individual violent crime incidents between 2013–2017 and across Philadelphia CBGs. We created five separate analytic datasets for each year of our study time period by combining credit score and violence CBG data with covariates from the US Census. We used Poisson regression to determine associations between CBG credit scores and CBG violent crime counts, after controlling for population density and percentages of home ownership, vacant houses, black residents, female-headed households, and poverty. Results: Across the five-year period, 27%-32% of CBGs had poor/fair credit score averages, 56–57% had good, and 12%-16% had excellent credit score averages. Moreover, violent crime counts per CBG across the five-year period ranged from 0–93 with a median of 8–10 incidents per CBG. CBGs with good credit scores had 18% - 28% less risk of violent crime compared to poor/fair credit CBGs. Furthermore, CBGs with excellent credit scores had a 36%-46% less risk of violent crime compared to poor/fair credit CBGs. Conclusions: Excellent and good credit score averages by CBG are associated with lower violent crime counts compared to CBGs with poor/fair averages across Philadelphia. Significance and Contributions to Injury and Violence Prevention Science: Credit scores have potential for improving the understanding of violence inequities and what contributes to violence, over and above traditional socioeconomic position measures.